Kesejahteraan pengemudi Grabbike online di Surabaya dalam perspektif maqashid al-shariah - Fanira Putri Dewantara Anwar; Ika Yunia Fauzia (Journal of Business & Banking, 2019)
The Welfare of Grabbike Online Drivers in Surabaya Perspective is studied in Maqashid Al-Shariah. This study examined the level of welfare of the Grabbike driver and was linked to the analysis of maqashid al-shariah. The data were colected  by interviewing, observin,  and documenting with the seven people as  informants. The data were analyzed using phenomenology and the truth was tested. The result shows  the level of welfare of the Grabbike driver is quite prosperous because the income they have earned from being a driver for Grabbike is sufficient for daily needs. However,  there were still informants who thought that the income from being a Grabbike driver was insufficient for daily needs. Most of the informants considered that his dharuriyat needs were fulfilled by working as a Grabbike driver. Although there are still informants who consider that their dharuriyat needs are not sufficient in terms of income earned by being a Grabbike driver, they are still mediocre.